1997
DOI: 10.1128/iai.65.2.551-556.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of aspartic proteases in disseminated Candida albicans infection in mice

Abstract: A murine model of disseminated candidiasis involving intranasal challenge with Candida albicans was developed and used to explore the role of C. albicans aspartic proteases as virulence factors during early dissemination. Pretreatment of neutropenic mice with the aspartic protease inhibitor pepstatin A by intraperitoneal injection afforded strong dose-dependent protection against a subsequent lethal intranasal dose of an aspartic protease-producing strain (ATCC 32354) of C. albicans. Administration of 0.6 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 25 publications
(34 reference statements)
3
29
1
1
Order By: Relevance
“…A significant dose-dependent protection against a subsequent lethal intranasal dose of C. albicans was observed by pretreatment of neutropenic mice with pepstatin A by intraperitoneal injection. The effect of pepstatin A was comparable to protection obtained with amphotericin B [41]. A reduced depth of invasion of parenchymal organs from the peritoneal cavity and the degree of tissue damage of peritoneal cavity by C. albicans was observed in mice pretreated with pepstatin A [42].…”
mentioning
confidence: 59%
“…A significant dose-dependent protection against a subsequent lethal intranasal dose of C. albicans was observed by pretreatment of neutropenic mice with pepstatin A by intraperitoneal injection. The effect of pepstatin A was comparable to protection obtained with amphotericin B [41]. A reduced depth of invasion of parenchymal organs from the peritoneal cavity and the degree of tissue damage of peritoneal cavity by C. albicans was observed in mice pretreated with pepstatin A [42].…”
mentioning
confidence: 59%
“…Although the host immune system is the major factor balancing the transition from commensalism to pathogenicity, several virulence attributes expressed by C. albicans, such as adhesion factors, phenotypic switching, dimorphic behaviour and secretion of hydrolytic enzymes (Fallow et al, 1997;Vargas et al, 2000;Calderone & Fonzi, 2001;Naglik et al, 2003;Romani et al, 2003;Consolaro et al, 2005), might contribute to the persistence of colonization and the development of symptomatic episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans causes several diseases, ranging from mucocutaneous to systemic infection. Various virulence factors contribute to pathogenesis; for example aspartyl proteases and phospholipases play an essential early role in C. albicans dissemination and enhance its ability to colonize deep organs (Fallow et al, 1997;Calderone & Fonzi, 2001), adhesins allow adherence to epithelial and endothelial cells (Naglik et al, 2003), and morphogenesis consists of reversible transitions between unicellular yeast cells and the filamentous growth forms that are present in clinical lesions (Kobayashi & Cutler, 1998;Romani et al, 2003;Consolaro et al, 2005). It has been demonstrated that Th cell reactivity plays a central role in regulating the immune response to C. albicans, Th1 reactivity being responsible for resistance and Th2 reactivity being associated with susceptibility (Nomi et al, 1994;Kaposzta et al, 1998;Romani, 1999).…”
Section: Introductionmentioning
confidence: 99%